The Implementation of Habit-Based Programs to Strengthen Moral Education in Primary Schools: A Case Study at SDN 7 Ampenan - Nabila, Siti Maulidiya; Farhanah, Baiq Chunafa Diza; Adiyatma, Fauzi Maha; Sumardi, Lalu (Journal of Education and Computer Applications, 2025)
Moral education serves as a fundamental pillar in shaping students’ character, particularly at the primary school level. This study aims to describe and analyze the implementation of a habit-based moral education program at SDN 7 Ampenan, a school situated within a complex social environment. Employing a qualitative approach with a case study design, data were collected through in-depth interviews, observations, and document analysis. The findings indicate that the programs Berbaris Kasih Sayang (Affectionate Morning Line-up), Upacara Pagi Spiritual (Spiritual Morning Ceremony), and the Literaksi Program are consistently implemented to instill moral values in students. Classroom strategies employed by teachers—such as providing positive affirmations, facilitating spiritual reflection, assigning daily moral tasks, and managing conflicts in an educational manner—further reinforce the internalization of moral values in students’ daily lives. The program has shown a significant impact, particularly on students from less supportive family backgrounds, by fostering self-confidence, empathy, and discipline. These findings highlight the importance of a structured habituation approach and emotionally supportive teacher-student relationships in the success of moral education. The study recommends the adoption of similar programs in other schools, with necessary adaptations to suit their respective social and cultural contexts.